The genus Neohydatothrips (Thysanoptera: Thripidae) in Iran with one new species and first record of a micropterous form - Minaei, Kambiz (Zootaxa, 2016)
Neohydatothrips amygdali sp. n. is described from southern Iran together with the first record of a micropterous form of Neohydatothrips abnormis (Karny). The new species is unusual among Sericothripinae in having only one pair of mid-dorsal setae on tergite IX. An illustrated identification key is provided to 5 species of Neohydatothrips namely, N. abnormis, N. amygdali, N. gracilicornis (Williams), N. gracilipes (Hood) and N. tadzhicus (Pelikan) from Iran.